Injuries from falls by older adults in long-term care captured on video: prevalence of impacts and injuries to body parts - Komisar, Vicki; Dojnov, Aleksandra; Yang, Yijian; Shishov, Nataliya; Chong, Helen; Yu, Ying; Bercovitz, Ian; Cusimano, Michael D.; Becker, Clemens; Mackey, Dawn C.; Robinovitch, Stephen N. (BMC geriatrics, 2022)
Falls are the leading cause of injuries in older adults. However, most falls in older adults do not cause serious injury, suggesting that older adults may fall in a manner that reduces the likelihood of impact to body sites that are most vulnerable to injury. In this observational study of falls in long-term care (LTC), we tested whether body parts differed in their probability of impact and injury.
Gesehen am 28.09.2022